Pengembangan Media Lauhul Qilab (Flip Chart) untuk Pengenalan Kosakata Bahasa Arab pada Anak TK/RA - Darojat, Rois Hidayah; Zukhaira, Zukhaira (Institut Agama Islam Negeri Curup, 2021)
This research is motivated by the introduction of Arabic at the Kindergarten/RA level, but the lack of effective and attractive media for the introduction of Arabic vocabularies in visual forms to children. The purposes of this reasearch are: (1) analyzing the teachers’ needs for the Lauhul Qilab (Flip Chart) media, (2) designing the prototype of Lauhul Qilab (Flip Chart) media, (3) analyzing the results of expert validation and improvements to the prototype of Lauhul Qilab (Flip Chart) media, and (4) analyzing the SWOT of the previous learning media with Lauhul Qilab (Flip Chart) media for the introduction of Arabic vocabularies. This research uses a Research and Development method. The stages passed in this research consist of five stages which encompass potentials and problems, data collection, product design, design validation, and design improvements. The subjects incorporated in this research are teachers and children of Kindergarten/RA in Semarang. The results of this research are: (1) the teachers want the development of 3-dimensional visual media for the introduction of Arabic vocabularies in group B in the Kindergarten. (2) The Lauhul Qilab (Flip Chart) media prototype is shaped like a sitting calendar which contains a front page title, instructions usage, material, and developer profile. (3) The results of expert validation include the aspects of material feasibility, language feasibility, presentation feasibility, and graphic feasibility with an overall average value of 87.20 (very feasible). (4) The Lauhul Qilab (Flip Chart) is one of the means of 3-dimensional visual media for the introduction of Arabic vocabulary that can complement the media that have been used by previous teachers, and it can increase children's creativity and interest in learning Arabic.